Elastases under Artificial Hypometabolism in Rats - Samokhina, L. M.; Lomako, V. V.; Shilo, A. V. (Problems of Cryobiology and Cryomedicine, 2008)
The development of artificial hypometabolism in rats contributes to tissue-specific rise in elastase activity, metalloeastase and decreased level of endothelial elastase. These changes are partially normalized in 24 hrs, herewith there was noted the participation of Î±-1-inhibitor of proteinases in suppressing of surplus activity of elastases.